Perilaku Pencegahan Kecelakaan Kerja Sebelum dan Sesudah Penyuluhan K3 Pada Perajin Batik - Hasanah, Maryam Uswatun; Setyaningsih, Yuliani; Lestantyo, Daru (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
Worker in the informal batik sector provide potential health risk in their work, such as exposure by synthetic chemicals that used in the production process of batik and un ergonomic working posture. The purpose of this study was determine the difference in knowledge, attitude and practice of prevention of workplace accidents before and after safety induction. It was use pre - experiment research method with pre and post test design. The population of this studied was to batik craftsman with totally numbers 14 people and the sample was taken as many as total of the population. The data were processed by bivariate Wilcoxon test analysed with the significance p<0,05. From the Wilcoxon statistical test found difference of knowledge (p = 0.002), difference of attitude (p = 0.003), and difference of accident in prevention practice before and after safety induction (p = 0.002). The result of this study showed difference of knowledge, attitude, and practice in prevention workplace accident before and after safety induction the batik craftsman in Kampung Batik Semarang.